2018
DOI: 10.1093/jas/sky042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, energy, and amino acid digestibility in 7 cottonseed co-products fed to growing pigs

et al.

Abstract: The objective of this study was to determine the chemical composition, DE and ME contents, and apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of AA in 7 cottonseed co-products fed to growing pigs. The 7 cottonseed co-products were: cottonseed meals (solvent extracted) with CP level of 46%, 50%, and 55% (46CSM, 50CSM, and 55CSM), cottonseed protein with CP level of 50% and 55% (50CSP and 55CSP), fermented cottonseed meal (CSMF), and expelled cottonseed meal (CSME). The DE and ME c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
3
5
0
Order By: Relevance
“…In the current study, DCP contained more Arg and Met and less Lys than FM and SPC; this finding was consistent with previous studies [1,8]. After the removal procedure, the free gossypol in DCP was significantly lower than that in CSM reported in previous literature with an average value of 300.94 mg/kg [16]. In addition, the tolerable level of free gossypol in growing-finishing pig diets was 100 mg/kg [17] and not reported in nursery pigs.…”
Section: Chemical Compositionsupporting
confidence: 93%
“…In the current study, DCP contained more Arg and Met and less Lys than FM and SPC; this finding was consistent with previous studies [1,8]. After the removal procedure, the free gossypol in DCP was significantly lower than that in CSM reported in previous literature with an average value of 300.94 mg/kg [16]. In addition, the tolerable level of free gossypol in growing-finishing pig diets was 100 mg/kg [17] and not reported in nursery pigs.…”
Section: Chemical Compositionsupporting
confidence: 93%
“…Cotton is grown in many parts of the world with global production of cotton seeds being 44 million tonnes per year which, after removal of oil, hulls and lint, provides approximately 15 million tonnes of cottonseed meal available for livestock (Soy and Oilseed Bluebook, 2015). However, cottonseed meal (CSM) can be of variable quality and in general has a poorer amino acid digestibility and availability than other oilseed meals (Prawirodigdo et al., 1998, Gonzalez-Vega and Stein, 2012, Ma et al., 2018), although the use of CSM in pig diets has been little researched (Stein et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, protein digestibility in piglets was more dependent upon the amino acid profile of the protein source rather than on other components in the diet including carbohydrates (Turlington et al., 1989). Moreover, wide variations in dietary protein content may influence the apparent ileal digestibility (AID) or total tract (ATTD) of nitrogen (N) or amino acids in growing pigs (Fan et al., 1994, Ma et al., 2018). Variation in processing technique can also contribute to variation in AID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Li et al. (2012) reported positive linear relationships between DE or ME and concentrations of CP and EE in cottonseed meal for growing pigs, and Ma et al. (2018) reported that DE increased from 3,152 to 3,702 kcal/kg of DM as the CP concentration of 5 cottonseed meals increased from 460 to 550 g/kg.…”
Section: Discussionmentioning
confidence: 91%